Estimation of the Relationship Between Exchange Rate and Domestic Consumption: Evidence from South African Red Meat Industry - Thaba, Tshephi Kingsley; Hlongwane, Jan Johannes (International Journal of Economics and Financial Issues, 2025)
The average individual experiences the value of currency as constant from day to day. The fact that the value of currency is constantly fluctuating in relation to other currencies only seems to matter for most people when planning for consumption. The purpose of the study is to examine the nexus between exchange rate changes and consumption of the south African red meat industry from 1995 until 2020, employing a time-series analysis. The paper used the secondary time series data for exchange rate volatility and red meat consumption. Descriptive statistics and Unit root test were performed for statistics and integration, respectively. Ordinal least square estimation was employed to determine the relationship. Furthermore, Granger causality test for directional causality effect. The overall conclusion from the results is that there is 1% change in total consumption that resulted from 0.04 percent change in exchange rate, so it can be conclude that exchange rate volatility has negative effects on domestic consumption. Exchange rate changes impact on consumption per capital, production, the volume of exports and industry’s employment. The study recommends that increasing local red meat production can help reduce dependence on imports, thereby insulating the industry from exchange rate volatility.